Household Waste Management Training To Improve The Economy Of Rural Communities - Butarbutar, Augustinus Robin; Dewi, Kemmala; Tahir, Usman; Krisdiyanto, Aris; Suparni, Sri (Universitas Pahlawan Tuanku Tambusai, 2024)
After discussing with fellow service members/writers involved in this article regarding organic waste management in order to improve the economy of rural communities. The result in this article show 1). Waste is the remains of daily human activities and/or from natural processes in solid form . The rate of waste production continues to increase, not only in line with the rate of population growth but also in line with the increase in people's consumption patterns. On the other hand, the waste handling capacity of the community and local government is not yet optimal. Waste that is not managed properly will affect the environment and the health of the surrounding community. 2). The concept of 3R waste management is no longer foreign to the public. This concept is very suitable to be applied in developing countries which, due to technological limitations, must empower communities as actors who produce waste. However, in reality the application of 3R in everyday life is still far from expected. The principle of Reduce, Reuse, Recycle (3R) which is the spearhead in dealing with waste in the community seems to be just a slogan that doesn't apply. 3). The author/devotee believes that rural communities are smart in utilizing waste from items that have no economic value into useful items that can even become a source of income for rural communities.